Quality of Life of an Adolescent Patient with Craniofacial Deformities Drug Addict Through Home Visits at the Tawanchai Center in Northeastern Thailand: A Case Report - Pradubwong, Suteera; Pakkasung, Yupin; Yimneum, Aporn; Samretdee, Hattakorn; Jaruensook, Wacharapong; Mungmanitmongkhol, Nannalin; Saentarana, Nongluk; Chowchuen, Bowornsilp (Srinagarind Medical Journal, 2024)
Background and Objective: This study focuses on a patient with congenital facial cleft with problems initiating initial illegal substance use. Therefore, home visits by a multidisciplinary team to monitor, identify, and resolve issues, as well as to improve her quality of life. Methods: Report a patient, involving a single home visit by a multidisciplinary team. The tools used in the study included: 1) the THAICLEFT quality of life questionnaire for patients with cleft lip and palate, 2) the Thai general health questionnaire, 3) the adolescent coping orientation for problem experience (ACOPE), and 4) the history of service use record form of the social work department. Data was collected in December 2023 and analyzed using descriptive statistics. Results: A female patient, aged 17 years-old, with high school education, having undergone surgery and orthodontic treatment. Family income was insufficient for daily expenses. Overall 4 dimensions, they exhibited high satisfaction with quality of life (4.42 ± 0.70), and minor family impacts (2.30 ±1.34). Substance abuse ceased, yet concerns regarding social interactions and a tendency toward depression were observed. Conclusion: Follow-up by home visit is helpful to understand the real causes of patients’ problems, and providing fundamental information that can be used to improve the quality of life for both the patients and their families.